Respostas
respondido por:
1
Sistemas - Método da Adição:
5t - 2m = 9 (I)
4t + 2m = 36 (+) (II)
9t = 45
t = 45/9
t = 5
Substitui em I:
5t - 2m = 9
5.5 - 2m = 9
25 - 2m = 9
25 - 9 = 2m
16 = 2m
2m = 16
m = 16/2
m = 8
5t - 2m = 9 (I)
4t + 2m = 36 (+) (II)
9t = 45
t = 45/9
t = 5
Substitui em I:
5t - 2m = 9
5.5 - 2m = 9
25 - 2m = 9
25 - 9 = 2m
16 = 2m
2m = 16
m = 16/2
m = 8
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás